2020
DOI: 10.24036/00261za0002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Adversity Quotient, Self Awareness and Demographic Factors to Student Career Maturity

Abstract: One of the purposes of vocational school (SMK) is as an education facility to prepare alumni who are ready to enter work field, but in contrary the highest number of unemployed in West Sumatra is dominated by SMK alumni. This research aims to describe the contribution of adversity quotient, self awareness and demographic factors to student career maturity. The study was conducted using quantitative descriptive methods. The research population were students of class XII at SMKN6 Padang as many as 392 students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
2
10
0
3
Order By: Relevance
“… 17 Moreover, the ability to face and overcome human obstacles is directly related to their physical and mental health because mental strength and self-control affect the body’s immune resistance and the individual’s self-care behaviors. 18 , 19 Kurniawan et al 20 explained that facing challenges and overcoming obstacles is indicated by a person’s ability to get up and act. Whether it is positive or negative for various situations, it depends on the individual whether there is more or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Moreover, the ability to face and overcome human obstacles is directly related to their physical and mental health because mental strength and self-control affect the body’s immune resistance and the individual’s self-care behaviors. 18 , 19 Kurniawan et al 20 explained that facing challenges and overcoming obstacles is indicated by a person’s ability to get up and act. Whether it is positive or negative for various situations, it depends on the individual whether there is more or less.…”
Section: Discussionmentioning
confidence: 99%
“…Whether it is positive or negative for various situations, it depends on the individual whether there is more or less. 20 Phoolka et al 21 also stated that healthy behaviors and adversity quotient, which are individuals, groups, organizations’ actions, and the relational factors and consequences of these actions. For instance, social change policy development and skill improvement actions coping and improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…High school students, particularly in the last classes, ought to be capable of focusing on their ideals and developing career goals based on their preferences and abilities. According to Kurniawan et al (2020), Career maturity includes characteristics or aspects that impact it, such as career planning, career exploration, knowledge of career choice making, understanding the world of work, knowledge about desired work groups, and career realization. Therefore, based on the findings of this research and past literature, career maturity is essential for high school students.…”
Section: The Impact Of Career Development Module On Career Maturity A...mentioning
confidence: 99%
“…The high degree of adversity quotient in fresh graduates enables individuals to confront these challenges, and the aim of obtaining a job will be achieved (Aprilia & Khairiyah, 2018;Drahs, Haywood, & Schiprowski, 2018). Besides that, the adversity quotient effectively contributes to students' career maturity by almost 23%, which will help the fresh graduates as job seekers during the pandemic (Kurniawan, Daharnis, & Karneli, 2020).…”
Section: Introductionmentioning
confidence: 99%